The Two-Way Relationship Between Calcium and Metabolism in Cancer - Dejos, Camille; Gkika, Dimitra; Cantelmo, Anna Rita (Frontiers in Cell and Developmental Biology, 2020)
Calcium ion (Ca2+) signaling is critical to many physiological processes, and its kinetics and subcellular localization are tightly regulated in all cell types. All Ca2+ flux perturbations impact cell function and may contribute to various diseases, including cancer. Several modulators of Ca2+ signaling are attractive pharmacological targets due to their accessibility at the plasma membrane. Despite this, the number of specific inhibitors is still limited, and to date there are no anticancer drugs in the clinic that target Ca2+ signaling. Ca2+ dynamics are impacted, in part, by modifications of cellular metabolic pathways. Conversely, it is well established that Ca2+ regulates cellular bioenergetics by allosterically activating key metabolic enzymes and metabolite shuttles or indirectly by modulating signaling cascades. A coordinated interplay between Ca2+ and metabolism is essential in maintaining cellular homeostasis. In this review, we provide a snapshot of the reciprocal interaction between Ca2+ and metabolism and discuss the potential consequences of this interplay in cancer cells. We highlight the contribution of Ca2+ to the metabolic reprogramming observed in cancer. We also describe how the metabolic adaptation of cancer cells influences this crosstalk to regulate protumorigenic signaling pathways. We suggest that the dual targeting of these processes might provide unprecedented opportunities for anticancer strategies. Interestingly, promising evidence for the synergistic effects of antimetabolites and Ca2+-modulating agents is emerging.